Iot-Based Remote Health Monitoring Systems (International Journal of Environmental Sciences, 2025)
Smart homes, smart cities, transportation, healthcare, education, and the military are some of the creative uses of the Internet of Things (IoT). IoT applications improve people's quality of life by providing safe, real-time remote patient monitoring, which makes them very useful in the healthcare industry. This review study looks at the most recent advancements in Internet of Things-based healthcare monitoring systems. Using sensor data and telecommunications, the Internet of Things (IoT) offers a useful and efficient way to track the health of senior citizens in real time. According to studies, the Internet of Things can provide a number of improved services when combined with smart technologies.Using technologies that allow for intelligent and remote wireless communication, researchers have developed a variety of emergency response systems. These developments have been used in many medical applications, especially in the field of older adult health monitoring, which has allowed for the collection of vital sign data and the detection of potentially hazardous situations.